Stability of Folate and Vitamin B12 in Human Serum after Long-Term Storage: A Follow-Up after 13 Years - Eugène H. J. M. Jansen; Piet K. Beekhof (Journal of Nutrition and Metabolism)
In epidemiological and nutrition research, it is very important to evaluate the stability of biomarkers as function of both storage time and temperature. In this study, the stability of folate and vitamin B12 in human serum samples has been tested after long-term storage at −80°C up to 13 years. Serum samples of 16 individuals were used in this study. The concentration of folate and vitamin B12 has been determined at t=0 and at 1, 8, and 13 years after storage at −80°C. The folate concentrations in serum samples remained stable at −80°C. The concentration of vitamin B12 was decreasing during the time of the study to about 50%. The correlation of the folate and also of the vitamin B12 concentrations in the stored samples compared with the starting values was still good. Therefore, although the concentration of vitamin B12 decreased upon storage, reliable comparative analyses can still be performed.